Trends of degradation and improvement in biomass productivity in target countries of CGIAR Initiative in Sustainable Intensification of Mixed Farming Systems – An Interim Report - Le, Quang Bao (International Center for Agricultural Research in the Dry Areas, 2022)
Trends of degradation and improvement in biomass productivity in the target countries of MFS Initiative using Trends.Earth tool. The calculation of the trends using global time-series of NDVI (MODIS) over the 2000-2015 period. Appropriate uses of the results for supporting other activities in MFS Initiative, as well as further validation with national experts are discussed and recommended.